1970
DOI: 10.1111/j.1476-5381.1970.tb10362.x
|View full text |Cite
|
Sign up to set email alerts
|

The Schultz‐Dale response of the longitudinal muscle strip preparation of guinea‐pig ileum

Abstract: Summary1. The mast-cell distribution in the various layers of the ileum has been described.2. Histamine-content, anaphylactic histamine-release and the anaphylactic dose-response curve of the full-thickness ileum and of the longitudinal muscle strip have been measured and compared. 3. Tetrodotoxin 10-7 g/ml had no obvious effect on the anaphylactic doseresponse curve of either preparation. This suggests that the plexus is not of any great importance in the Schultz-Dale reaction. 4. Exposure of the longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

1978
1978
1992
1992

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
0
22
2
Order By: Relevance
“…In contrast to this report [22], these agents were later found to block not only the Schultz-Dale reaction of guinea-pig ileum, but also histamine [23]. Considering the low specificity of yohimbine, gramine and bufotenine [23]; inability to show the release of 5-HT by antigen from sensitized guinea-pig ileum [23,25,34,47]; resistance of the anaphylactic reaction of guineapig ileum to hexamethonium [43], atropine [ and LSD [23]) and tachyphylaxis to 5-HT [49], it seems reasonable to suggest that 5-HT and acetylcholine probably do not participate in anaphylactic contractions of guinea-pig ileum. Recently, it has been reported that the Schultz-Dale reaction of chicken ileum is resistant to atropine, methysergide and tachyphylaxis to 5-HT which suggests that cholinergic and tryptaminergic mechanisms are not important in this tissue [100].…”
Section: A Pharmacology Of the Schultz-dale Anaphylactic Response (Icontrasting
confidence: 73%
See 2 more Smart Citations
“…In contrast to this report [22], these agents were later found to block not only the Schultz-Dale reaction of guinea-pig ileum, but also histamine [23]. Considering the low specificity of yohimbine, gramine and bufotenine [23]; inability to show the release of 5-HT by antigen from sensitized guinea-pig ileum [23,25,34,47]; resistance of the anaphylactic reaction of guineapig ileum to hexamethonium [43], atropine [ and LSD [23]) and tachyphylaxis to 5-HT [49], it seems reasonable to suggest that 5-HT and acetylcholine probably do not participate in anaphylactic contractions of guinea-pig ileum. Recently, it has been reported that the Schultz-Dale reaction of chicken ileum is resistant to atropine, methysergide and tachyphylaxis to 5-HT which suggests that cholinergic and tryptaminergic mechanisms are not important in this tissue [100].…”
Section: A Pharmacology Of the Schultz-dale Anaphylactic Response (Icontrasting
confidence: 73%
“…1,A,i) [43]. The decrease in numbers of mast cells, release of histamine and complete inhibition of antigen-induced contraction by mepyramine or by prior treatment with octylamine (a potent histamine releaser) suggest that histamine is an important mediator in anaphylactic response of this tissue [43].…”
Section: A Pharmacology Of the Schultz-dale Anaphylactic Response (Imentioning
confidence: 97%
See 1 more Smart Citation
“…There are significant stores of histamine in mast cells located at the periganglionic sheaths in the myenteric plexus in the guinea-pig small intestine, and this histamine can be released during anaphylaxis in vitro and presumably in vivo (Dale & Zilletti, 1970). Putative messenger substances in the gastrointestinal tract such as substance P, neurotensin and somatostatin are known to release histamine from mast cells (Johnson & Erdos, 1973;Oishi, Ishiko, Inagaki & Takaori, 1983;Renner, 1982;Skofitsch, Donnerer, Petronijevic, Saria & Lembeck, 1983;Theoharides & Douglas, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Like other parts of the nervous system, there are indications that the functional integrity of the enteric system may be influenced by neuronal actions of histamine. In the small intestine, histamine is present in mast cells with greatest amounts in the mucosal regions and with small but significant amounts in mast cells that are situated in close association with the ganglia of the myenteric plexus (Dale & Zilletti, 1970). Application of histamine evokes contractions of longitudinal muscle-myenteric plexus preparations from guinea-pig small intestine (Barker & Ebersole, 1982;Zaveez & Yellin, 1982) and evokes increases in chloride secretion by the guinea-pig small intestinal mucosa (Cooke, Nemeth & Wood, 1984).…”
Section: Introductionmentioning
confidence: 99%